Mekanisme (Sumber) Koping Pada Ibu yang Mengalami Baby Blues Syndrome di RS. Elim Rantepao - Tulak, Lulu Alang; Yusriani, Yusriani; Idris, Fairus Prihatin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Maternity blues classified as mild psychological disorders that are sometimes experienced by postpartum mothers. To cope with maternity blues, the mother can adopt coping mechanisms. This study aims to determine coping mechanisms in mothers who experienced maternity blues in Elim Rantepao Hospital. Type this study is a qualitative study with descriptive approach. The participants consisted of five main informants that mothers who experienced maternity blues, 3 participants support (family), and one key participant (midwife who cared for). Research results obtained show that how mother cope with stress is also highly dependent on the resources available, such as family support mothers serve as the source of the greatest coping, besides spiritual beliefs, social support, balance of energy and material, also used as a source her coping. But things are different are obtained, is heir belief or trust in which the mother perform rituals or believe to get a peace, for that in the face of maternity blues, it needed the support of the coping resources that mothers do not continue in conditions more severe disorders.